Allogeneic chimeric antigen receptor-modified cells for adoptive cell therapy of cancer. (July 2014) - Marcus, Assaf; Eshhar, Zelig
<x xml:space="preserve">Abstract</x> Introduction: Chimeric antigen (or antibody) receptors (CAR) are fusion proteins typically combining an antibody-derived targeting fragment with signaling domains capable of activating immune cells. Recent clinical trials have shown the tremendous potential of adoptive cell transfer (ACT) of autologous T cells engineered to express a CD19-specific CAR targeting B-cell malignancies. Building on this approach, ACT therapies employing allogeneic CAR-expressing cytotoxic cells are now being explored. Areas covered: The basic principles of CAR-ACT are introduced. The potential benefits as well as problems of using allogeneic CAR-modified cells against tumor antigens are discussed. Various approaches to allogeneic CAR therapy are presented, including donor leukocyte infusion, CAR-redirected γδ T cells and natural killer cells, strategies to avoid graft-versus-host disease, modulation of lymphocyte migration, and exploitation of graft-versus-host reactivity. Expert opinion: CAR-modified allogeneic cells have the potential to act as universal effector cells, which can be administered to any patient regardless of MHC type. Such universal effector cells could be used as an 'off-the-shelf' cell-mediated treatment for cancer.